Risk Assessment of Genetically Engineered Maize Resistant to Diabrotica spp.: Influence on Above-Ground Arthropods in the Czech Republic - Svobodová, Zdeňka; Skoková Habuštová, Oxana; Hutchison, William D; Hussein, Hany M; Sehnal, František (PloS one, 2015)
Transgenic maize MON88017, expressing the Cry3Bb1 toxin from Bacillus thuringiensis (Bt maize), confers resistance to corn rootworms (Diabrotica spp.) and provides tolerance to the herbicide glyphosate. However, prior to commercialization, substantial assessment of potential effects on non-target organisms within agroecosystems is required. The MON88017 event was therefore evaluated under field conditions in Southern Bohemia in 2009-2011, to detect possible impacts on the above-ground arthropod species. The study compared MON88017, its near-isogenic non-Bt hybrid DK315 (treated or not treated with the soil insecticide Dursban 10G) and two non-Bt reference hybrids (KIPOUS and PR38N86). Each hybrid was grown on five 0.5 ha plots distributed in a 14-ha field with a Latin square design. Semiquantitative ELISA was used to verify Cry3Bb1 toxin levels in the Bt maize. The species spectrum of non-target invertebrates changed during seasons and was affected by weather conditions. The thrips Frankliniella occidentalis was the most abundant species in all three successive years. The next most common species were aphids Rhopalosiphum padi and Metopolophium dirhodum. Frequently observed predators included Orius spp. and several species within the Coccinellidae. Throughout the three-year study, analysis of variance indicated some significant differences (P<0.05). Multivariate analysis showed that the abundance and diversity of plant dwelling insects was similar in maize with the same genetic background, for both Bt (MON88017) and non-Bt (DK315) untreated or insecticide treated. KIPOUS and PR38N86 showed some differences in species abundance relative to the Bt maize and its near-isogenic hybrid. However, the effect of management regime on arthropod community was insignificant and accounted only for a negligible portion of the variability.
Keywords: Coleoptera; rezistence k insekticidům; Endotoxins; geneticky modifikované rostliny; Zea mays; genetické inženýrství; Animals; Insecticide Resistance; biologická kontrola škůdců; zvířata; Pest Control, Biological; Risk Assessment; Plants, Genetically Modified; Genetic Engineering; hodnocení rizik; kukuřice setá; insekticidy; endotoxiny; brouci; Insecticides